Pemuliaan Mutasi untuk Perbaikan terhadap Umur dan Produktivitas pada Kedelai - Asadi Asadi (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2013)
To support the government policy inimproving soybean production, it is suggested to plant earlymaturing (<80 days), drought tolerant and high yieldingvarieties to be applied in the cropping system of rice-ricesoybeanand rice-rice-rice-soybean in lowland, and indryland cropping system of rice-soybean or rice-otherpalawija crops. Mutation breeding in soybean for earlymaturity and high productivity in soybean can be applied toobtain some new varieties. The breeding proceduresincluded selection using bulk method for M1 population,followed by the pedigree method for M2-M5 generations.Evaluation of uniformity (homozygous) of lines is done onthe M4 generation. Yield and adaption testing are conductedduring M5-M8 generations. Through mutation breeding earlymaturity soybean varieties were released elsewhere. Innational research institutes such as The National NuclearEnergy Agency (Batan) Indonesia, soybean mutation breedingactivities were begun since 1972, while in IndonesianCenter for Agricultural Biotechnology and GeneticResources Research and Development (ICABIOGRAD), itwas started in 2009. Batan has released two early maturingsoybean varieties through seed irradiation such as Tenggerin 1991 and Meratus in 1998. While in 2011 ICABIOGRADthrough irradiation of calli-derived embryo zygotic hasselected 50 early maturing and potentially yielding soybeanmutant lines. While through seed irradiation in 2012, 15soybean advanced lines that matured earlier anddemontrated higher yield were also obtained.